Predicting thermal response of conductive foods during start-up of process equipment using transfer functions - Ansorena, Maria Roberta (2010)
Transfer function approach to predict thermal histories of conductive foodstuffs when surroundings present different forcing functions during start-up of process are reported. Food is assimilated to a delayed first order system with unit gain and characterize by two parameters, the dead time (L) and the time constant (t). The comparison of experimental data and the proposed models for cooking as well as for retorting processes presented very satisfactory results when the equipment evolved as first order, second order and bounded integrating systems.